2018
DOI: 10.3390/genes9110522
|View full text |Cite
|
Sign up to set email alerts
|

Valproic Acid Inhibits Proliferation and Reduces Invasiveness in Glioma Stem Cells Through Wnt/β Catenin Signalling Activation

Abstract: Glioblastoma is the most common malignant brain tumour in adults. The failure of current therapies can be ascribed to glioma stem cells (GSCs), which can rapidly repopulate the tumour following the initial treatment. The study of histone deacetylase inhibitors, such as valproic acid (VPA), is becoming an attractive field in cancer research. However, the exact mechanisms underlying its anti-cancer effect remain to be elucidated due to its pleiotropic effects on several cell-signalling pathways. Ingenuity Pathwa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 29 publications
(25 citation statements)
references
References 46 publications
(71 reference statements)
1
21
0
1
Order By: Relevance
“…The GSC lines (GBM2, G144, G166, GBM04) were isolated from patients affected by glioblastoma and characterized for their stemness properties from a genetic and molecular point of view (Baronchelli et al, 2013). All the GSC lines were already expanded in vitro as stable cell lines and used as powerful model for studying their biology and testing drug susceptibility, furthermore their cytogenomic and epigenomic profiles were well characterized (Riva et al, 2014, 2018; Cilibrasi et al, 2017). GSC were cultured in adherent culture condition using 10 mg/ml laminin (Invitrogen) in a proliferation permissive medium composed by DMEM F-12 and Neurobasal 1:1 (Invitrogen), B-27 supplement without vitamin A (Invitrogen), 2 mM L-glutamine, 10 ng/ml recombinant human bFGF and 20 ng/ml recombinant human EGF (Miltenyi Biotec), 20 UI/ml penicillin and 20 g/ml streptomycin (Euroclone; complete medium).…”
Section: Methodsmentioning
confidence: 99%
“…The GSC lines (GBM2, G144, G166, GBM04) were isolated from patients affected by glioblastoma and characterized for their stemness properties from a genetic and molecular point of view (Baronchelli et al, 2013). All the GSC lines were already expanded in vitro as stable cell lines and used as powerful model for studying their biology and testing drug susceptibility, furthermore their cytogenomic and epigenomic profiles were well characterized (Riva et al, 2014, 2018; Cilibrasi et al, 2017). GSC were cultured in adherent culture condition using 10 mg/ml laminin (Invitrogen) in a proliferation permissive medium composed by DMEM F-12 and Neurobasal 1:1 (Invitrogen), B-27 supplement without vitamin A (Invitrogen), 2 mM L-glutamine, 10 ng/ml recombinant human bFGF and 20 ng/ml recombinant human EGF (Miltenyi Biotec), 20 UI/ml penicillin and 20 g/ml streptomycin (Euroclone; complete medium).…”
Section: Methodsmentioning
confidence: 99%
“…Rampazzo et al (Rampazzo et al, 2013) found that Wnt/β-catenin mediated the reprogramming of GBM cells toward a neuronal-like fate. Intriguingly, a recent study demonstrated that VPA can affect the canonical Wnt/β-catenin pathway (Riva et al, 2018), a highly conserved signaling pathway that has been thought to play pivotal roles in stem cell self-renewal and embryogenesis modulation (Nusse et al, 2008; van Amerongen and Nusse, 2009; Riva et al, 2018) and whose aberrant activation has been identified in a range of cancers (Duchartre et al, 2016; Zhan et al, 2017), including GBM (Zhang et al, 2012). Impairment of the canonical Wnt signaling pathway is observed frequently in patients with GBM (Zhang et al, 2012) and is associated closely with GBM development, invasiveness, and progression (Gong and Huang, 2012; Kahlert et al, 2012; Kierulf-Vieira et al, 2016).…”
Section: Potential Molecular Mechanisms Underlying the Anticancer Promentioning
confidence: 99%
“…VPA is an inhibitor of histone deacetylases (HDACs) and has pleiotropic effects on many biological processes such as cancer cell growth arrest, proliferation, differentiation, invasion, apoptosis, immune system, and neuroprotection [ 32 , 33 , 34 , 35 , 36 , 37 ]. Several studies indicate that HDAC inhibitors may be promising therapeutic agents for neurodegenerative diseases [ 38 , 39 ].…”
Section: Discussionmentioning
confidence: 99%